Oncogene and tumor-suppressor gene products as serum biomarkers in occupational-derived lung cancer. (September 2007) - Helmig, Simone; Schneider, Joachim
Since lung cancer is the most frequent occupational cancer and one of the leading causes of cancer mortality in the world, it is one of the biggest challenges for research. In the literature, there are inconsistent results regarding the utility of the serum biomarkers p53, anti-p53 antibodies, EGF receptor or Ras. Based on the published results, routine use of these biomarkers for detection of occupationally derived lung carcinomas is not currently recommended. In this review, we summarize the literature and discuss the relevance of these oncogene and tumor-suppressor gene products as serum biomarkers in occupational-derived lung cancer.